The ambulatory battery of creativity: Additional evidence for reliability and validity - Rominger, Christian; Fink, Andreas; Benedek, Mathias; Weber, Bernhard; Perchtold-Stefan, Corinna M.; Schwerdtfeger, Andreas R. (Frontiers in Psychology, 2022)
Psychometrically sound instruments that assess temporal dynamics of creative abilities are limited. The Ambulatory Battery of Creativity (ABC) is designed to assess creative ideation performance multiple times in everyday life and was proven to capture the intra-individual dynamic of creative abilities reliably and validly. The present ambulatory study aimed to replicate and extend the psychometric evidence of the novel ABC. Sixty-nine participants worked on the ABC during a 5-day ambulatory assessment protocol. Each day, participants completed six randomly presented items of the verbal and the figural ABC. Matching previous psychometric analyses, the results indicated good between-person (≥.81) and good within-person (≥.72) reliability. Furthermore, evidence for between-person and within-person validity of the ABC was obtained. Performance in the verbal and the figural ABC were interrelated and correlated with an independent measure of creative potential. The verbal ABC was further associated with openness, self-reported creative behavior, creative activities, and creative achievements, thus providing additional evidence of construct validity, especially for the verbal ABC. Finally, the verbal and the figural ABC yielded convincing within-person validity: Longer response times and higher subjective originality ratings were associated with more original ideas. This replication and extension of the ABC’s psychometric properties indicates that it enables a reliable and valid assessment of moment-to-moment fluctuations of creative ideation abilities in everyday life, which may facilitate the investigation of exciting new research questions related to dynamic aspects of creative ability.